An examination of members’ intentions to recommend fitness centres - Gonçalves, Celina (2017)
In the sports industry, service recommendation is pivotal due to its impact on the organizations’ profitability (Alexandris et al., 2004). Recommendation is a way of expressing positive behavioral intentions towards the organization, and several studies have focused on understanding its antecedents (Ferrand et al., 2010). For example, perceptions of service attributes and accessibilities (Chelladurai & Chang, 2000) have been highlighted as vital aspects guiding behavioral intentions, including service recommendations. Additionally, recent studies suggest that well-being in life is related to consumption levels in a variety of settings, while well-being in the fitness club tends to contribute to positive behavioral intentions towards the club (Barros & Gonçalves, 2009). While previous studies have focused on measuring each of these variables separately, little is known about the simultaneous effects of these variables. This is a vital aspect to provide a global understanding of how to improve members’ recommendations in fitness consumption environments. Drawing on previous literature, the purpose of this study is to examine the antecedents of service recommendations in an integrated model, including the attributes of the service, accessibilities, well-being in life and well-being in the fitness club. The study sample consisted of paid members from one the biggest Portuguese fitness networks. Based on the conceptual dimensions proposed in the literature, a survey with 18 items was created with the cooperation of a panel of specialists including two Portuguese club managers and two professors of sport management from a mid-sized Portuguese University. Service attributes were measured using 5 items (e.g. innovative equipment), while accessibilities were assessed using 2 items (e.g. good location). These items were designed by the experts. Well-being in life (5 items) and well-being in the club (5 items) were based on Diener et al. (1997). Service recommendation was measured using a single item based on Alexandris et al. (2004). The use of a single item is consistent with previous studies (Ferrand et al., 2010). All items were measured with a 5-point Likert-type scale (1=strongly disagree, to 5=strongly agree). The surveys were distributed by an experienced interviewer in seven clubs located in four different cities. Members were asked to participate in a study when arriving the club, and the surveys were self-administered in a room near the reception desk. A total of 2,500 surveys were collected and, after data screening, 1,750 were deemed usable for data analysis. Data were submitted to a two-step maximum likelihood structural equation model (AMOS 20.0). The results of the measurement model indicated an acceptable fit to the data [χ²(113)=493.99 (p<.001), CFI=.98, GFI=.97, RMSEA=.04]. The composite reliability values of the constructs were above the cut-off point of .70, while AVE values were greater than .50 providing evidence of convergent validity. Discriminant validity was accepted given that the AVE value for each construct was greater than the squared correlations between that construct and any other. Additionally, the overall assessment of the structural model indicated an acceptable fit to the data [χ²(126)=547.92 (p<.001), CFI=.98, GFI=.97, RMSEA=.04]. The results indicate that service attributes (β=.22, p<.01) and well-being in club (β=.54, p<.01) have a significant positive effect on recommendations. Accessibilities did not show a significant relationship with recommendation (p>.05), while well-being in life showed a significant negative effect on recommendation (β=-.09, p<.01). The ability of the hypothesized model to explain variation in the outcome variable was assessed through the R2 value (R2recommendation=48%). The findings are consistent with previous studies suggesting that the perceptions of service attributes are vital to increase recommendations (Ferrand et al., 2010). Additionally, well-being in club was the strongest predictor of recommendations highlighting the role of delivering the service in pleasant environments. Based on the items of this study, fitness managers should keep innovating in terms of the facilities and equipment, showing interest in solving member’s needs in order to ensure they feel good in the club, and thus, increasing their intentions to recommend the club. In turn, the findings did not show a significant role of the accessibilities dimension, which may be due to the good accessibilities of the clubs tested in the study. All clubs of this fitness network are located in central areas of the cities, and thus, a good accessibility may be seen as pre-requisite of the service provided by the club. On the other hand, well-being in life showed a negative effect on recommendations. These findings should be considered by fitness managers when designing marketing strategies for increasing the number of members, and provide opportunities to continue advancing our knowledge of how to manage fitness clubs.